De novo and recessive forms of congenital heart disease have distinct genetic and phenotypic landscapes - W. Scott Watkins (Nature Portfolio, 2019)
Large whole-exome sequencing studies have suggested that the genetic architecture of syndromic congenital heart disease (CHD) is different from sporadic forms. Here, Watkins et al. estimate the relative contribution of damaging recessive and de novo genotypes to CHD in 2391 trios and find them to be associated with different gene functions.